Redeployment of specialist surgeons in the COVID-19 pandemic in a general hospital: critical issues and suggestions - Ferrara, Fabrizio; Galmarini, Valter; Tosco, Piermario; Molinari, Giampaolo; Capelli, Roberto Maria (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: to gain experience and highlight any margins for improvement, we outlined the role played by specialist surgeons (with particular reference to orthopedic surgeons), redeployed in treating COVID-19 patients in the Emergency Department of a general hospital, with severe overcrowding due to the massive and continuous arrival of patients Methods: “on the field” experience of the Authors is reported, followed by a narrative review of the literature, mainly on the topic of health-personnel redeployment during an emergency Results: a brief chronological discussion of the progressive reorganization of the hospital, in relation to the progress of the epidemic in the area, is reported, with specific reference to the experience of orthopedic and other branches specialist surgeons, that was characterized by a high degree of uncertainty about what to do, worsened by organizational difficulties due to the incessant arrival of patients and subsequent overcrowding. Observations relating to the critical aspects that have emerged and the various solutions proposed or implemented, if they have been identified, as well as the problems still open, are then made and compared to current literature. Conclusions: The most significant aspect that we have tried to outline is the organizational difficulty, due to the rapid and unpredictable change in the situation: greater efficiency and flexibility, seen as the ability to overcome bureaucratic, logistical, regulatory or budgetary obstacles that prevent the rapid changes made necessary by the epidemic, could perhaps help to face better any subsequent pandemic wave, like the fierce one ongoing at the present moment